Histomorphometric Analysis of Osseointegrated Intraosseous Dental Implants Using Undecalcified Specimens: A Scoping Review - Stefan Peev; Ralitsa Yotsova; Ivaylo Parushev (Biomimetics)
Bone histology and histomorphometry are reliable diagnostic tools for the assessment of the bone–implant interface, material safety and biocompatibility, and tissue response. They allow for the qualitative and quantitative analysis of undecalcified bone specimens. This scoping review aims to identify the most common staining techniques, study models for in vivo experiments, and histomorphometric parameters used for quantitative bone evaluation of osseointegrated dental implants in the last decade. The Web of Science, PubMed, and Scopus databases were searched on 1 July 2024 for relevant articles in English, published in the last ten years, and the data were exported to an MS Excel spreadsheet. A total of 115 studies met the eligibility criteria and were included in the present review. The results indicate that the most common study models are dogs, rabbits, and pigs. Some of the most frequently used methods for the assessment of the bone–implant interface are the Toluidine blue, Stevenel’s blue with Van Gieson, and Levai–Laczko stainings. The results from this study demonstrate that the most commonly used histomorphometric parameters in implant dentistry are the bone-to-implant contact (BIC), bone area fraction occupancy (BAFO), bone area (BA), and bone density (BD). This review presents the recent trends in histomorphometric analysis of dental implants and identifies some research gaps that necessitate further research.